Reverse plasticity: TGF‐β and IL‐6 induce Th1‐to‐Th17‐cell transdifferentiation in the gut. Issue 10 (October 2016) - Geginat, Jens; Paroni, Moira; Kastirr, Ilko; Larghi, Paola; Pagani, Massimiliano; Abrignani, Sergio
Abstract : Th17 cells are plastic and can upregulate IFN‐γ production, and thus transdifferentiate to either Th1/17 cells in response to IL‐1 and IL‐23, or to exTh17‐Th1 cells in response to IL‐12. Liu et al. showed in the European Journal of Immunology for the first time that Th1 cells show a similar plasticity and could transdifferentiate to Th1/17 cells in the presence of TGF‐β, IL‐6, IL‐1β and IL‐23, and to exTh1‐Th17 cells in the presence of TGF‐β and IL‐6. This alternative pathway of Th17‐cell generation is likely to have important implications for both immune‐mediated diseases and for protective immune responses in the gut. Abstract : Th17 cells are a heterogeneous population of pro‐inflammatory T cells that have been shown to mediate immune responses against intestinal bacteria. Th17 cells are highly plastic and can transdifferentiate to Th1/17 cells or unconventional Th1 cells, which are highly pathogenic in animal models of immune‐mediated diseases such as inflammatory bowel diseases. A recent European Journal of Immunology article by Liu et al. ( Eur. J. Immunol . 2015. 45:1010–1018) showed, surprisingly, that Th1 cells have a similar plasticity, and could transdifferentiate to Th17 cells. Thus, IFN‐γ‐producing Th1 effector cells specific for an intestinal microbial antigen were shown to acquire IL‐17‐producing capacities in the gut in a mouse model of colitis, and in response to TGF‐β and IL‐6 in vitro. TGF‐β induced Runx1, and together with IL‐6 was shown to render the ROR‐γt and IL‐17 promoters in Th1 cells accessible for Runx1 binding. In this commentary, we discuss how this unexpected plasticity of Th1 cells challenges our view on the generation of Th1/17 cells with the capacity to co‐produce IL‐17 and IFN‐γ, and consider possible implications of this Th1‐to‐Th17‐cell conversion for therapies of inflammatory bowel diseases and protective immune responses against intracellular pathogens.